Konsep Manusia Dan Kebahagiaan - Yusi Tri Hastuti; Sri Haryati; Kasori Mujahid (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Humans are one of the many creatures created by God who are given many advantages over other creatures, apart from being special, humans are also unique and complete creatures. Every human being in his life will have aspirations to achieve happiness. Human happiness cannot be measured by worldly things, worldly happiness is temporary. To obtain true happiness, humans must rely on the Islamic way of life, namely the Qur'an and Hadith, which prioritize the goal of happiness in the afterlife and is the main happiness compared to other happiness, because it is haqiqi (eternal). The source of true happiness in Islam is tranquility. heart and soul comfort, in order to obtain the peace in question, Muslims must first increase their faith in Allah SWT, because faith in the heart will create inner and outer calm and happiness. With trials in the world, humans will always be calm because if they are tested with goodness they will be grateful and if they are tested with evil they will be patient. Both will receive rewards. So people don't need to be sad if they haven't found happiness in this world, as long as they always prepare life provisions for happiness in the hereafter.